The participation of Vhembe District Community Corrections Forum (CCF) members in the re-integration of ex-offenders - Magadze, Tshimangadzo Oscar (Acta criminologica, 2017)
The Department of Justice and Correctional Services (DJCS) in South Africa has endorsed a community participation policy to achieve re-integration objectives, but the challenge remains on the implementation process in order to reduce recidivism. The higher the success rate of ex-offenders’ re-integration, the fewer recidivists will be re-admitted and, consequently, the correctional centre population will be reduced. This study seeks to contextualise the participation of Community Corrections Forum members in the re-integration of ex-offenders into the community in Vhembe District. Currently, there is a lack of community involvement into ex-offenders’ re-integration which makes it difficult for ex-offenders to settle back into their communities. The introduction of Community Corrections Forums (CCFs) is not effective and the policy is silent about their objectives during the re-integration process. The involvement of community members in re-integration of ex-offenders assist the DJCS to facilitate community with the goal of successful re-integration.